Imparting effective Teaching Learning Methods for teaching C programming course to First Year Non-IT Students - Patil, Pragati; Jadhav, Priyanka; Kanase, Minakshee (Journal of Engineering Education Transformations, 2025)
Nowadays, Computers are the dominant technology of the twenty-first century. Thus, programming and the development of software are fundamental activities in which many people across the globe are involved. As a result, programming courses are part of the curriculum. The course is introduced to all first-year IT and Non-IT students who have either no or less expertise in computer programming. The main purpose to select these techniques for non-IT students is to prepare them to work with IT specialists at their future jobs by instilling in them a constant knowledge of technical fundamentals. But as compared to IT students, learning of C programming becomes difficult for non-IT students due to this their passing rate is low. Students lose their interest in programming due to their having less computer programming knowledge which leads to a gap in technical competency require by the IT sector. Taking this into consideration activities like quizzes, debugging tests, and usage of a virtual lab for students were implemented. These activities enhanced students’ way of thinking, problem-solving ability, programming, and debugging skills. The idea of using PBL teaching methods, Think-Pair-Share, and E-Learning may improve the effect of C language teaching, and promote the student’s learning initiative. The main focus of this study is to enlighten different teaching approaches and methodologies for first-year non-IT students.